Factors affecting labour productivity, skilled labour and return to education in Malaysia - Mohamad Yunus, Norhanishah (2014)
The importance of human capital, research and development (R&D) and technology spillovers have been widely recognised by the Malaysian government as a potential engine to achieve a productivity driven economy. Given that the skill and knowledge become an important source to achieve higher productivity towards developed country, hence, Malaysia emphasises investment in human capital, R&D and the role of technology in their long and medium term plans. For the first objective, this study aims to delve deeper into the impact of investment in human capital and R&D in influencing labour productivity in 53 manufacturing industries during the period of 2000 to 2008. The present study employs the SYS-GMM technique to estimate the labour productivity function. The result finds that the cost of training sponsored by employers and educational attainment with degrees levels are positive and significant in influencing labour productivity in manufacturing industry. The result also shows that R&D investment is negatively correlated with labour productivity, but it is statistically significant in influencing labour productivity. The findings on the importance of investment in human capital and R&D provide recommendations for government to design financial incentives and favourable tax policies that encourage individuals and employers to invest in post-compulsory education and in-service training for all workers. Regarding the negative correlation between R&D investment and labour productivity, government is encouraged to enhance further the provision of public education on the development of science, technology and engineering skills to increase the absorptive capacity amongst local workers to adopt the new technology. Malaysia has recognised that the process of skill upgrading and development of technology capacity can be integrated with foreign direct investment (FDI) and trade, because both channels have their spillover effects that are embodied in terms of technology and knowledge. In spite of Malaysia is among the major FDI recipient countries of the South East Region, but the benefit of the FDI spillovers to skill upgrading remains ambiguous. Hence, the second objective in this study is to investigate the effect of technology spillovers via FDI and trade for skill upgrading and thus increase the relative demand for skilled labour in 50 Malaysian manufacturing industries during the period of 2000-2008. After controlling for endogeneity by using the SYS-GMM estimator, the results confirm that the technology spillovers via FDI is significant for skill upgrading and in turn leads to an increase in demand for skilled labour. Even though the FDI coefficient indicates a negative correlation between FDI and skilled labour demand, but the effect of technology spillovers via FDI as indicated by FDI2 is statistically positive and significant . This gives an indication that the effect of technology spillovers via FDI appears to be assimilated quickly by the workers in the Malaysian manufacturing industry through ―learning effect‖ and the fast pace is biased towards skilled workers. Nevertheless, this study finds no evidence of technology spillovers via trade in influencing the demand for skilled labour.The findings from this study can potentially contribute to the long-run FDI policy, especially to encourage FDI inflows into low receiving industries. The Malaysian Government has also given recognition to the importance of individual to make investment in education. Education increases the productivity of workers by imparting useful knowledge and skills as well as a main determinant of individuals to increase their earning potential is timely. Higher earnings are closely associated with additional education that can be thought of as a rate of return on educational investment. In line with these facts, the third objective in this study attempts to investigate the return to education at different levels of the highest certificate achieved in six economic sectors under the National Key Economic Areas (NKEA) in 2002, 2004 and 2007. They are; financial sector, business services sector, education sector, wholesale and retail sector, electrical and electronics (E&E) sector and communications content and infrastructure (CCI) sector. This study employs the OLS estimator with robust standard error . The results from the estimation of earning function can be concluded as follows: First, this study finds that the average return to education is highest for workers with degree qualifications in the financial, education, wholesale (except in 2002), CCI and E&E sectors (except in 2007) throughout the sample period. This result indicates that the average return to education increases with the level of highest certificate, and there is a match between occupation and qualification. Secondly, the result finds that over-education occurs in financial and wholesale sectors despite the largest average return enjoyed by the degree holders compared to their counterpart. Average return to education for over-educated workers shows a somewhat increasing trend between 2002 and 2007; perhaps the over qualification that they possess enables them to perform better for lower-skilled job and thus contributes to increase the firm‘s productivity. Thirdly, the result finds that the average return to education for workers with primary education comes as the highest average return for earners only in the E&E sector in 2007. The reasoning is deemed plausible when explaining the highest average return to education for primary workers because the E&E sector‘s activities are more concentrated on the assembly line and test stages, which is the lower value-added part of the E&E sector. Lastly, the result shows a decline in the average return to education at the degree qualification level between 2002 and 2007 in the E&E and CCI sectors. The declining return in both sectors is due to the shortfall in the skills available among workers when adapting to the dynamic and evolving nature of the industry as well as the emerging new technology that changes over time. Consequently, the requirements for any new entrée into an industry might be upgraded and the workers who are already employed will appear to be under-skilled. Another reason for the declining return of workers with degree qualifications is due to the supply of workers with this qualification for medium-skilled occupation, which is now outstripping the supply of workers at high-skilled jobs; thus leaving the graduate workers to willingly undertake the non-graduate job. Such willingness, however, will drag down the average return for degree-educated workers because they might be dissatisfied with their current job, and this would lower the firm‘s productivity. The findings from this study may contribute to solving the problem of mismatch between the education qualification and the skill demand in a firm, as the number of students completing their study at all levels of qualification keeps increasing year by year. The overall findings in this study conclude that education, trained and skilled workforce, R&D investment and technology spillovers via FDI play a major role in enhancing labour‘s skills and knowledge, which in turn increases Malaysia‘s productivity and economy growth.